• Math background
  • Math background
  • Mathematics background
  • Mathematics background
  • Fundamentals of Statistics
  • Math graphics free wallpaper in free desktop
  • stock vector : math background
  • Math background, discrete math
  • Free Math Background for Powerpoint Slides
  • Royalty-Free (RF) Clipart Illustration of a Math
  • Mathematica -photos of some famous historical figures
  • binary system
  • Pascals triangle.
  • Conic section
  • Welcome to mathematics
  • Taylor polynomials and Taylor series -
  • ... theory of Taylor series to show that the
  • The Unit Circle
  • Graphs of the functions sin(x) and cos(x),
  • GOne of the applications of the zeta function
  • Taylor Series Approximation Illustrated
  • Matematik eğitiminin sağlıklı
  • crazy math(12)
  • crazy math(11)
  • crazy math(10)
  • crazy math(9)
  • crazy math(8)
  • crazy math(7)
  • crazy math(6)
  • crazy math(5)
  • crazy math(4)
  • crazy math(3)
  • crazy math(2)
  • crazy math(1)
  • Mickeys ears are circles which are conic sections

مسألتين على حل معادلات فى مجهولين فى صورة مقادير مركبة

السبت، 13 أكتوبر، 2012 التسميات:
المعادلة الاولى
X^2 + Y^2 + X i - Y i = 13 + i


والمعادلة الثانية
XY + ( 3X+Y) i = 2 + 5 i

العدد المركب = جزء حقيقى + جزء تخيلى
وبناء على هذا فالمسألة توضع فى ابسط
صورة ومن ثم تكون المقارنة على طرفى المعادلة
بين الجزئين الحقيقى والتخيلى .

x² + y² + i x + i y = 13 + i

نستطيع ان نقول الضرب الأيمن موضوع فى
الصورة القياسية له : عدد حقيقى + عدد تخيلى .
بقى لنا ان نصنع ذلك ايضاً من الطرف الأيسر بحيث
ننقله الى صورة أخرى (صورة العدد المركب)

x² + y² + i(x+y) = 13 + i

وهذا يعنى ما يلى :

x² + y² = 13     ==>  1
x + y = 1      ==>  2

بحل النظامين معاً بأى طريقة مناسبة لك فينتج
لنا كلاً من قيم x , y  .

وانا افضل الحل بهذه الطريقة ...

==> بتحليل معادلة (1) : l    (x+y)² - 2xy = 13

ولكن x+y = 1        بالتعويض ..

1²-2xy = 13  ومنها   xy = -6

فأصبح من اليسير جداً تكوين معادلة تربيعية
فى متغير افتراضى وليكن z بحيث حلول z
هى حلول x,y  .

ان لم تكنب تفهم هذه الطريقة استخدم احدى
طرق التعويض .. من معادلة (2)  x+y = 1

اذاً  y = 1 - x   بالتعويض فى xy = -6

x(1 - x) = -6   ومنها   x - x² + 6 = 0

بضرب الطرفين فى سالب :  x² - x - 6 = 0

بالتحليل :  l         (x - 3) (x + 2) = 0

x = 3    او  x = -2

بالتعويض فى y = 1 - x

y = 1 - 3 = -2   او  y = 1 + 2 = 3

الملخص : x = 3  عندما  y = -2
            x = -2 عندما  y = 3

========================
حل المسألة الثانية نفس الفكرة تقريباً ..

XY + ( 3X+Y) i = 2 + 5 i

xy = 2     ==>   1
3x+y = 5 ==>   2

من (2) :  y = 5 - 3x  بالتعويض فى (1)

x(5 - 3x) = 2  قم بفك القوس ...

5x -3x² - 2 = 0   بضرب الطرفين فى سالب (مع الترتيب)

3x² - 5x + 2 = 0     بتحليل المقدار الثلاثى ..

l            (3x - 2) (x - 1) = 0

اما  x = 1    أو    x = 2/3

بالتعويض فى : y = 5 - 3x

y = 5 - 3(1) = 2  أو  y = 5 - 3(2/3) = 3

أى أن : x = 1   عندما  y = 2
        x = 2/3  عندما y = 3‏

0 التعليقات:

إرسال تعليق

 
mathematics problem solving © 2010 | تعريب وتطوير : سما بلوجر | Designed by Blogger Hacks | Blogger Template by ياعرب